2000
DOI: 10.1097/00008877-200002000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the acute effects of cigarette smoking on the reinforcing value of alcohol

Abstract: Alcohol consumption acutely increases smoking behavior, but the reverse relationship, the acute effects of smoking on alcohol intake, largely has been ignored. We examined whether smoking acutely increases the reinforcing value of alcohol, first in the absence of recent alcohol intake and then following an alcohol pre-load. Healthy, social-drinking smokers (n = 11 men, 14 women) engaged in a computerized task involving concurrent schedules of reinforcement for beer (FR10, 3 oz (90 ml) per reinforcement) or mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 31 publications
3
46
2
Order By: Relevance
“…First, the sample size was modest and only generalizeable to the population of heavy-drinking daily smokers. Although our sample size was comparable to other laboratory studies examining the effect of nicotine replacement on alcohol responses (e.g., Acheson et al 2006;Barrett et al 2006;Perkins et al 1995Perkins et al , 2000a, our analyses for gender comparisons were under-powered. Second, only a single priming dose was investigated.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…First, the sample size was modest and only generalizeable to the population of heavy-drinking daily smokers. Although our sample size was comparable to other laboratory studies examining the effect of nicotine replacement on alcohol responses (e.g., Acheson et al 2006;Barrett et al 2006;Perkins et al 1995Perkins et al , 2000a, our analyses for gender comparisons were under-powered. Second, only a single priming dose was investigated.…”
Section: Discussionmentioning
confidence: 90%
“…Human laboratory studies have examined the effect of smoked tobacco on alcohol use (Barrett et al 2006;Madden et al 1995;Mello et al 1980Mello et al , 1987 as well as the effect of nicotine deprivation on the reinforcing value of alcohol (Colby et al 2004;Cooney et al 2003;Palfai et al 2000;Perkins et al 2000a). Fewer studies have tested the effect of nicotine replacement on subjective alcohol responses (Cooney et al 2001;Kouri et al 2004;Perkins et al 1995) and alcohol self-administration behavior (Acheson et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kouri et al (2004) reported that men pretreated with a 21-mg nicotine patch before ingesting alcoholic beverages had markedly higher subjective reports of feeling drunk, feeling the effects of alcohol and wanting to drink more than subjects given alcohol alone. Additionally, Perkins et al (2000) found that men who smoked cigarettes after recently consuming alcohol significantly increased responding for more alcohol compared to those who did not smoke. They also found that those in the smoking group indicated greater subjective stimulatory and reduced sedative effects of alcohol compared to controls (Perkins et al 2000; see also Rose et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, Perkins et al (2000) found that men who smoked cigarettes after recently consuming alcohol significantly increased responding for more alcohol compared to those who did not smoke. They also found that those in the smoking group indicated greater subjective stimulatory and reduced sedative effects of alcohol compared to controls (Perkins et al 2000; see also Rose et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…That is, alcohol may facilitate smoking, or nicotine may facilitate drinking. Indeed, there is experimental evidence that ethanol increases the reinforcing properties of tobacco smoking and nicotine (i.e., Griffiths et al 1976;Mintz et al 1985;Mitchell et al 1995;Rose et al 2004), and there is limited evidence that nicotine may increase the reinforcing value of ethanol (Barrett et al 2006;Perkins et al 2000;Potthoff et al 1983;Smith et al 1999).…”
Section: Introductionmentioning
confidence: 99%